Study of Plant Pest Organisms in Maize-Edamame Intercropping - Siti Afiyana Damayanti; Mahindra Dewi Nur Aisyah; Iqbal Erdiansyah; Christa Dyah Utami (KHD Production, 2025)
The problem of maize-edamame cultivation is inseparable from the attack of plant pest organisms. Another alternative control is needed, one of which is the intercropping. This study aims to observe pests that attack glutinous maize and edamame plants. This research was conducted from June to September 2024 on farmland on Kebonsari, Sumbersari District, Jember Regency. The experimental design used was by comparing polyculture and monoculture planting patterns consisting of 4 treatments. The results showed the presence of pests and diseases, namely aphids (Aphis glycines), green looper (Chrysodeixis chalcites), asian maize borer (Cercospora sojina), stem borer (Ostrinia fumacalis), southern rust (Puccinia sorghi) and or maize smut (Ustilago maydis).